Case selection biases in management research: the implications for international business studies. (1st September 2010) - Collinson, Simon; Rugman, Alan M.
This paper reports on a bibliometric analysis of peer-reviewed articles in business and management studies, initially conducted in 2004 and repeated in 2009. It reveals that a small number of firms (11 in 2004) account for over 50% of the total 'hit count' for all firms in our list of the largest 200 multinationals. The major implication of this finding is that we gain most of our academic insights and our 'best-practice' lessons on management from a small, unrepresentative group of 'exemplar' companies. Seven case selection biases are identified, showing a disproportionate focus on a sub-set of firms that are: global and bi-regional; US-based; large; manufacturers; in dominant positions in important industries; long-term survivors; owners of strong brands. In this paper, we examine the first of these biases most closely. We conclude that business and management studies tend to overestimate the benefits and underestimate the difficulties of internationalisation.